Ballast weight review of capsule husk Jatropha curcas Linn. on acid fermentation first stage in two phase anaerobic digestion - Adinurani, Praptiningsih G.; Setyobudi, Roy Hendroko; Wahono, Satriyo Krido; Mel, Maizirwan; Nindita, Anggi; Purbajanti, Endang Dwi; Harsono, Soni Sisbudi; Malala, Andoniana Rakoto; Nelwan, Leopold O.; Sasmito, Andi (Pakistan Academy of Sciences, 2017)
Increasing biogas production through the use of Dried Capsule Husk - Jatropha curcas Linn. (DH-JcL) as raw materials study was conducted at PT Bumimas Ekapersada experiment field, in Bekasi, West Java, Indonesia from September 2013 to March 2014. Four HDPE pipes with 5 L volume used as first stage-hydrolysis digester, while an HDPE (high-density polyethylene) drum with working volume 80 L was used as second phase - methanogenesis digester. DH-JcL at the first stage was pressed by a 1 800 g ballast, which was to be compared to a 900 g ballast pressed, diluted in water with volume ratio of 1:8. One third of the second stage digester was filled by immobilized growth of random packing system on special plastic design. Organic Loading Rate was predetermied at 3 000 cc · d–1 with Hydrolic Retention Time of 4 wk. This study was repeated three times and conclusion was made using t test as inferential statistics. The test concluded that 900 g ballast produced the best result. DH-JcL biogas productivity is increased, by two phase system, as much as 163 % when compared to semi continuous single phase system. Furthermore, the set up produces methane content higher (90 % to 91 %) than semi continuous single phase system (83.15 %). VFA average decrease of 16 %, and average alkalinity decreased by 11 %. Average ratio of VFA/ alkalinity is 0.5 similar with semi continuous single phase system.